2006
DOI: 10.1093/jac/dkl241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluconazole consumption on long-term trends in candidal ecology

Abstract: Despite long-term exposure to fluconazole, no change in candidal ecology was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 10 publications
7
30
2
Order By: Relevance
“…In another study Fournier et al reported a significantly higher proportion of C. parapsilosis due to prior exposure to caspofungin [25]. In contrast, Blot et al reported no change in Candida species [26]. Therefore, more studies are required to understand the interplay of the factors responsible for any shift in Candida species distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In another study Fournier et al reported a significantly higher proportion of C. parapsilosis due to prior exposure to caspofungin [25]. In contrast, Blot et al reported no change in Candida species [26]. Therefore, more studies are required to understand the interplay of the factors responsible for any shift in Candida species distribution.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Antimicrobial resistance was defined 24,27,28 as resistance to fluconazole for Candida species, as resistance to methicillin for staphylococci, as resistance to vancomycin for enterococci, as resistance to ampicillin for streptococci, as production of extended-spectrum ÎČ-lactamases for Enterobacter species, and as resistance to 1 of the following agents for gram-negative nonfermenting bacteria: ceftazidime, piperacillin, ciprofloxacin, imipenem, or meropenem.…”
Section: Definitions and Outcome Measuresmentioning
confidence: 99%
“…Candida glabrata is the most significant species that has emerged and now regularly ranks number two, after C. albicans, as the etiologic agent of superficial and invasive candidiasis occurring in adults (17,27). Reasons for this change in species distribution remain uncertain but may be partially due to the natural resistance of C. glabrata to azole derivates, widely used since the 1980s (6,10,26). This lower susceptibility of C. glabrata to azoles (2,23,38) and delayed initiation of therapy due to delayed diagnosis (2,20,35) may explain in part why the prognosis for C. glabrata candidemia is worse than that for C. albicans candidemia (7,18,41,51).…”
mentioning
confidence: 99%